Life Skills as Determining Factors for Academic Benefits among Adolescents - Sultan, Sarwat; Saleem, Muhammad; Durrani, Areeha Khan (University of Wah Journal of Social Sciences, 2021)
This study was objectified to investigate the impact of life skills on academic benefits; academic self-efficacy, academic resilience and academic chievement of adolescents. For this purpose, a sample of 360 school students were randomly selected from six schools provided data on Life Skills Scale (Vranda, 2009), Academic Self-Efficacy Scale (Gafoor & Ashraf, 2007), and Academic Resilience Scale (Martin & Marsh, 2006) along with demographic information and percentages of class test scores (Academic Achievement). The collected data were analyzed through SPSS (24.0) and findings from multivariate analysis showed the significant impact of life skills on academic outcomes. The results demonstrated the significant effects of following seven life skills; decision making, problem solving, self-awareness, interpersonal skills, communication skills, creative thinking and critical thinking had significant impact on academic self-efficacy, academic resilience and academic achievement of adolescents. The findings of current study have the implications for teachers and psychologists who can increase the academic benefits among adolescents by exerting these generic life skills.